15 Epicardial fat in diabetes mellitus and cardiovascular disease measured using cardiac magnetic resonance imaging: a summit substudy. (17th November 2015) - Maniam, P; Weir-McCall, JR; Cassidy, DB; Al-Talabany, S; Colhoun, HM; Houston, JG
Abstract : Background: Ectopic fat stored in the epicardium has previously been associated with coronary heart disease. However the role of type-2 diabetes mellitus (T2DM) in epicardial fat deposition has not been well explored. This study compares the volume of epicardial and paracardial fat in a T2DM cohort with and without cardiovascular disease (CVD) and matched non-diabetic cohorts. Methods: A cohort of 158 participants were categorised into one of 4 groups: 1-T2DM with CVD; 2-T2DM without CVD; 3-CVD without T2DM; 4-Healthy controls. Measurements were performed on 4 chamber cardiac magnetic resonance (CMR) images using Segment (v2.0-R4339 (http://segment.heiberg.se ). Epicardial adipose tissue (EAT) was defined as fat within the visceral pericardium while paracardial adipose tissue (PAT) was defined as fat out with the parietal pericardium. Results: In total, 148 participants completed the MRI study protocol (61% male, 64 ± 8.2 years). EAT was highest in those with CVD without diabetes (15.2 ± 6.6 cm 2 ), followed by those with T2DM and CVD (14.3 ± 6.4 cm 2 ), then those with T2DM only (13.1 ± 4.6 cm 2 ) with healthy controls having the lowest EAT (10.8 ± 5.0 cm 2 ) (F = 3.5, p = 0.016). No difference between the groups was observed for PAT (F = 2.1, p = 0.1). Post-hoc analysis showed only the non-diabetic CVD group to have significantly higher EAT than the healthy controls with no other significant differences between the groups. These differences persisted when accounting for differences in BMI between the groups (ANCOVA F = 2.9, p = 0.038). Conclusion: EAT was higher in non-diabetics with CVD, but not in T2DM with or without CVD. This suggests EAT may play a greater role in CVD in non-diabetics than those with T2DM.